Carotid atherosclerosis in virologically suppressed HIV patients: comparison with a healthy sample and prediction by cardiovascular risk equations. Issue 7 (5th April 2021) - Saumoy, M; Di Yacovo, S; Pérez, S; Sánchez‐Quesada, JL; Valdivielso, JM; Subirana, I; Imaz, A; Tiraboschi, JM; García, B; Ordoñez‐LLanos, J; Benítez, S; Podzamczer, D; et al.
Abstract : Objectives: To compare the prevalence of carotid atherosclerosis in virologically suppressed HIV patients with that of a community sample, and to evaluate the capacity of various cardiovascular risk (CVR) equations for predicting carotid atherosclerosis. Methods: This was a cross‐sectional study with two randomly selected groups: HIV patients from an HIV unit and a control group drawn from the community. Participants were matched by age (30–80 years) and sex without history of cardiovascular disease. Carotid plaque, common carotid intima–media thickness (cc‐IMT) and subclinical atherosclerosis (carotid plaque and/or cc‐IMT > 75 th percentile) were assessed by carotid ultrasound. The Systematic Coronary Risk Evaluation (SCORE), Framingham, REGICOR, reduced Data Collection on Adverse Effects of Anti‐HIV Drugs (D:A:D), and COMVIH equations were applied, and their abilities to predict carotid plaque were compared using the area under the curve (AUC). Results: Each group included 379 subjects (77.8% men, age 49.7 years). Duration of antiretroviral therapy was 15.5 years. There were no differences between the groups for carotid plaque (HIV, 33.2%; control, 31.3%), mean cc‐IMT (HIV, 0.63 mm; control, 0.61 mm) or subclinical atherosclerosis (HIV, 42.9%; control, 47.9%). Thymidine analogues were independently associated with subclinical atherosclerosis in HIV‐infected patients. CVR equations revealed AUCs between 0.715 and 0.807 for prediction of carotid plaque; prediction was better in the control group and did not improve when HIV‐adapted scales were used. Conclusions: The features of carotid atherosclerosis did not differ between the HIV‐infected and the control group, although CVR equations were more predictive for carotid plaque in controls than in HIV‐infected patients. HIV‐specific equations did not improve prediction.